ANALISIS PERBUATAN WANPRESTASI PIHAK PENYEWA DALAM PERJANJIAN SEWA-MENYEWA RUMAH (STUDI KASUS PUTUSAN MAHKAMAH AGUNG RI NO. 1507 K/PDT/2010) - Dewi Fitri (PREMISE LAW JURNAL, 2013)
Leasing is a mutual agreement by each party which causes a bond to each other. The case which is ruled by the Supreme Court of the Republic of Indonesia No. 1507 K/PDT/2010 indicates that there has been land leasing relationship since December 20, 1959. The claim of the case occurred because the heir of the lessee stopped paying for the rent and because the heirs of both parties did not renew the agreement; therefore, the relationship was cancelled by law. This case is stipulated in Article 2 and Article 21, paragraph (1) of the Government Regulation No. 44/1994 on House Occupation by Non-Owner which states that house occupation by non-owner is valid when there is an agreement or permission by the owner, and housing leasing contract, written or unwritten, which does not mention the time limit and had occurred before Law No. 4/1992 was enacted, is declared dissolved within three years since the law is enacted.